2004
DOI: 10.1086/383203
|View full text |Cite
|
Sign up to set email alerts
|

The Western and Eastern Roots of the Saami—the Story of Genetic “Outliers” Told by Mitochondrial DNA and Y Chromosomes

Abstract: The Saami are regarded as extreme genetic outliers among European populations. In this study, a high-resolution phylogenetic analysis of Saami genetic heritage was undertaken in a comprehensive context, through use of maternally inherited mitochondrial DNA (mtDNA) and paternally inherited Y-chromosomal variation. DNA variants present in the Saami were compared with those found in Europe and Siberia, through use of both new and previously published data from 445 Saami and 17,096 western Eurasian and Siberian mt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
178
3
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(203 citation statements)
references
References 102 publications
15
178
3
7
Order By: Relevance
“…In contrast with nuclear estimates, there is higher variance among villages. The lowest mtN e is found in CAR, where mtN e is slightly above 2000, about three times smaller than Saami (a traditional isolated group 16 ). The second feature revealed by the EBSP analysis is a constant demography for villages, again in accordance with nuclear estimates.…”
Section: Population Clusteringmentioning
confidence: 80%
See 1 more Smart Citation
“…In contrast with nuclear estimates, there is higher variance among villages. The lowest mtN e is found in CAR, where mtN e is slightly above 2000, about three times smaller than Saami (a traditional isolated group 16 ). The second feature revealed by the EBSP analysis is a constant demography for villages, again in accordance with nuclear estimates.…”
Section: Population Clusteringmentioning
confidence: 80%
“…Finally, we also included published mtDNA controlregion data from the Saami, a northern population known to be a genetic outlier among Europeans. 16 …”
Section: Subjects and Methods Samplesmentioning
confidence: 99%
“…14 Several genetic studies have been conducted to shed light on the genetic origin of the Saami. [15][16][17][18] These studies suggested that the Saami are descendants of Europeans who, several thousand years ago, reached northern Fennoscandia from both a western and an eastern route and subsequently got admixed. They also found a small East Asian contribution to the gene pool.…”
Section: Introductionmentioning
confidence: 99%
“…They also found a small East Asian contribution to the gene pool. 18,19 Several genetic studies have further suggested that the extent of linkage disequilibrium (LD) in the Saami is dramatically higher compared to that of outbred populations. [20][21][22][23] Higher levels of LD are observed in other population isolates as well.…”
Section: Introductionmentioning
confidence: 99%
“…This mutation, previously observed by Thomas et al (1996) was found to be in connection with A12308G (a marker for mtDNA haplogroup U), T3197C (a marker for haplogroup U5), and T5814C (which was associated with mitochondrial encephalopathy; Manfredi et al, 1996) in a patient with limb myopathy (Sternberg et al, 1998). Indeed, it is now well known that a transition at position 5656 (which is located as a non-coding spacer between the tRNA Ala and tRNA Asn genes) is characteristic of a sub-haplogroup (now referred to as U5b1; Tambets et al, 2004) of the European haplogroup U5b (Finnilä et al, 1999(Finnilä et al, , 2001Herrnstadt et al, 2002). Phylogenetic information is thus a useful guide to the evaluation of pathogeneity of a particular mutation, especially since the database of complete mtDNA sequences is rapidly growing; e.g.…”
mentioning
confidence: 99%